Clear Air and Precipitation Millimeter-Wave Point-to-Point Wireless Link Prediction Based on Terrain Path Profile in Semi-Arid Climate - Ahmed Shamsan, Zaid (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents a 38-GHz point-to-point wireless link prediction study using terrain path profile and aims to be used for the foreseen radio communication planning and design in a new metropolitan constructed area in Riyadh, Saudi Arabia, which is a semi-arid region. Point-to-point link simulations were made using both of Longley-Rice and ITU-R P.530 models to help designing reliable wireless broadband solutions so that wireless broadband service providers can consistently fulfill or exceed performance expectations. As the assumed link is in a semi-arid climate, it is characterized by low precipitation rates. However, these rates can cause downtime on the radio link due to using millimeter-waves which experience high fading. For the link availability study and analysis, many technical parameters are considered including different field measured rain rates, a various transmitter (Tx) antenna heights, elevation and land cover data (terrain profiles between the Tx and the receiver (Rx)), antenna coverage, etc. The results showed that the fade margin tends to be smaller at lower antenna height due to the absence of the clear line of sight (LOS), and at high precipitation rates caused by the high attenuation in millimeter-waves. Additionally, it has been found that the link will be unavailable when the rain rate of R(0.01) or more is exceeded. Furthermore, it has been shown that the highest link availability percentage for the positive fade margin is 99.997% and 99.993% in clear air and the precipitation rate of R(0.25) conditions, respectively.